Effect of particle size on silver nanoparticle deposition onto dielectric barrier discharge (DBD) plasma functionalized polyamide fabric - Vu, Nguyen Khanh (2013)
The effect on the deposition of three different size silver nanoparticles (AgNPs) onto a polyamide 6,6 (PA) fabric pre-treated using air dielectric barrier discharge (DBD) plasma was investigated. The SEM, EDS, and XPS analysis confirm that the smaller is the diameter of AgNPs, the higher the amount of adsorbed NPs on the PA. The DBD treatment on PA induces a threefold increase in Ag adsorption. The result confirms a dual effect on the wettability of the plasma treated PA substrate. AgNPs slightly enhance hydrophobicity of the PA surface and, at the same time, protect it against the plasma aging effect. The effect on the deposition of three different size silver nanoparticles (AgNPs) onto a Polyamide 6,6 (PA) fabric pre-treated using air dielectric barrier discharge (DBD) plasma was investigated. The smaller is the size, the higher the loaded AgNPs. The DBD treatment induces a threefold increase in Ag adsorption. AgNPs enhance hydrophobicity of the PA surface and reduce the plasma aging effect.